2016
DOI: 10.1111/andr.12246
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles in testicular biopsies of patients with impaired spermatogenesis

Abstract: Spermatogenesis is a complex process that involves thousands of genes whose expression during different stages is strictly regulated. Small non-coding microRNAs play an important role in the posttranscriptional regulation of mRNA processing during spermatogenesis. Using Agilent SurePrint v16 microRNA 8 × 60 K microarray kit, we investigated the microRNA expression profiles of 24 formalin-fixed paraffin-embedded testicular biopsies from patients with hypospermatogenesis (n = 10), hypospermatogenesis and azoospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Since it was not possible to detect HPV DNA in the testicular biopsies from unselected azoospermic men in the present study, HPV is probably not a frequent cause of azoospermia. To highlight the aetiologies of azoospermia, and particularly NOA not explained by other probable causes, it might be relevant to evaluate other factors than HPV, for example possible genetic factors (Stouffs et al, ) including the expression of microRNA (Noveski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Since it was not possible to detect HPV DNA in the testicular biopsies from unselected azoospermic men in the present study, HPV is probably not a frequent cause of azoospermia. To highlight the aetiologies of azoospermia, and particularly NOA not explained by other probable causes, it might be relevant to evaluate other factors than HPV, for example possible genetic factors (Stouffs et al, ) including the expression of microRNA (Noveski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously compared this kit with the RNA isolation method using the Trizol reagent and with two other commercial kits for RNA isolation only; we had found that the AllPrep DNA/RNA FFPE Kit was best suited for our needs because the obtained RNA samples were of consistent quality and that the RNA samples contained small RNAs of sufficient quality and quantity that enabled us to perform miRNA microarray expression study. 8 RNA quantity and purity were determined using the NanoDrop ND-2000 (NanoDrop Technologies, Wilmington, DE, USA), and RNA integrity (as RNA integrity number, RIN) was assessed using the RNA 6000 Nano Chip on a Bioanalyzer 2100 (Agilent Technologies, Santa Clara, CA, USA). The isolated RNA was analyzed using the Human Male Infertility RT 2 Profiler PCR Array (Cat# PAHS-165ZC; Qiagen), which profiles the expression of 84 key gene transcripts detected in the male germline that are known to be involved in different fertility-and sperm-related processes in the cell, including spermatogenesis, fertilization, male sex differentiation, cell motility, cell cycle and response to stress.…”
Section: Rna Isolation Quality Control and Performance Of Real-time mentioning
confidence: 99%
“…In addition to the classical post‐transcriptional control by RNA‐binding proteins, some studies have demonstrated that small non‐coding micro‐RNAs (miRNAs) may have a crucial role in regulating different stages of spermatogenesis 9‐11 …”
Section: Introductionmentioning
confidence: 99%
“…Most studies on miRNAs involve animal models and only a few investigate miRNAs expression in humans with different histopathological patterns of testicular dysfunction 11,13 …”
Section: Introductionmentioning
confidence: 99%